Corruption offenses in the university system of developed and developing countries: comparative legal aspect - Amandykova, S.K.; Altynbasov , B.O. (Bulletin of the Karaganda University “Law Series”, 2019)
The article examines the essence of corruption offenses in the field of education in the context of developed and developing countries, and also provides a comprehensive overview of some anti-corruption measures of the government and real problems. Corruption in developed countries is different from corruption in develop-ing and underdeveloped countries. Noting the influence of the main factors of corruption in developing coun-tries, he determines its causes and consequences. He focuses on theoretical approaches that help classify and respond to corruption in developed countries. According to Transparency International, corruption practices in the CIS as well as in Italy, Australia, Malaysia and Thailand are relatively legal. As part of the article, cor-ruption is a form of corruption in higher education, such as bribery, illegal personal education, loss of proper-ty, fraud, coercion, care, clannishness, favoritism, negligence, fraud, plagiarism, illegal research behavior, negligence, circumvention of criteria, monetary compensation for the «dead soul», termination of the con-tract, misleading information, loss of state property, monopolization of scientific publications and the distri-bution of textbooks, includes inefficiencies explicit allocation of resources. The study focuses on the need to identify and diagnose certain universal signs of corruption in order to combat corruption. Technical measures to combat corruption offenses include the development of new rules and regulations governing the behavior of teachers, the introduction of a more transparent reporting system and the creation of independent agencies for conducting exams and tests for students.